Language, regulation, and practice in the informational linguistic landscape of Bogor Botanical Garden - Oentari, Brigitta Sita (LITERA, 2026)
The objective of this research is to explore the informational linguistic landscape of Bogor Botanical Garden as a synchronic signage study. As a heritage site governed by national regulations with diverse visitors, the botanical garden provides a relevant case study for exploring how language can be used to exercise control and regulate public space. Based on the informational functions defined by Landry and Bourhis (1997), part writing identified by Backhaus (2007) and code preference analysis described by Scollon and Scollon (2003), this paper investigates signs that primarily perform informational functions, namely information signs, prohibition and warning signs, advertising signs, and street signs. The signs are classified according to the sign taxonomy proposed by Spolsky and Cooper (1991). The findings show that the Indonesian language is dominant within all the taxonomies, as it constitutes the primary language of regulation and control. The English language supports international accessibility, while the Latin language is commonly employed as a scientific language in plant-related signs. Other languages, such as Sundanese, Arabic, French, and Dutch, are used selectively for promotional and contextual purposes. This study contributes to linguistic landscape research by analyzing botanical garden as an underexplored setting and by emphasizing how institutional regulation, scientific communication, and tourism impact language functions within a public space in Indonesia.